A research and evaluation capacity building model in Western Australia - Lobo, R.; Crawford, Gemma; Hallett, J.; Laing, S.; Mak, D.; Jancey, J.; Rowell, S.; McCausland, K.; Bastian, L.; Sorenson, A.; Tilley, P.; Yam, S.; et al. (2016)
Evaluation of public health programs, services and policies is increasingly required to demonstrate effectiveness. Funding constraints necessitate that existing programs, services and policies be evaluated and their findings disseminated. Evidence-informed practice and policy is also desirable to maximise investments in public health. Partnerships between public health researchers, service providers and policymakers can help address evaluation knowledge and skills gaps. The Western Australian Sexual Health and Blood-borne Virus Applied Research and Evaluation Network (SiREN) aims to build research and evaluation capacity in the sexual health and blood-borne virus sector in Western Australia (WA). Partners' perspectives of the SiREN model after 2 years were explored. Qualitative written responses from service providers, policymakers and researchers about the SiREN model were analysed thematically. Service providers reported that participation in SiREN prompted them to consider evaluation earlier in the planning process and increased their appreciation of the value of evaluation. Policymakers noted benefits of the model in generating local evidence and highlighting local issues of importance for consideration at a national level. Researchers identified challenges communicating the services available through SiREN and the time investment needed to develop effective collaborative partnerships. Stronger engagement between public health researchers, service providers and policymakers through collaborative partnerships has the potential to improve evidence generation and evidence translation. These outcomes require long-term funding and commitment from all partners to develop and maintain partnerships. Ongoing monitoring and evaluation can ensure the partnership remains responsive to the needs of key stakeholders. The findings are applicable to many sectors.